Penerapan Model Pembelajaran Discovery Learning Berbantuan Media Ulartangga untuk Meningkatkan Hasil Belajar Siswa - Suparya, I Ketut (STAHN Mpu Kuturan Singaraja, 2023)
The learning process by inviting students to play will give students happiness. If students feel happy, it will be easier to provide cool learning material. The existence of an independent curriculum also provides opportunities for teachers and students to always develop innovation in learning activities. This study aims to find out the application of the Discovery learning model assisted by snakesladders media in order to improve the learning outcomes of class IVB students at Elemntary School Number 1 Penatih. This study consists of two cycles, which is each cycle consisting of four stages, namely planning, action, observation/evaluation, and reflection. The subjects of this study were 32 students of grade IVB Elementary School Number 1 Penatih. The object of this study is the result of the learning in topic 3. The method in collecting the data in this study is the test method of learning outcomes. Based on the results of this study, it can be concluded that the average percentage of learning outcomes in topic 3 reaches 40% and classical completeness reaches 40%. After applying the Discovery learning model assisted by snakesladders media in cycle I, the average percentage of learning outcomes reached 65%, and classical completeness reached 65%. With the improvement in cycle II, the average percentage of students' Topic 2 learning outcomes increased to 90% and classical completeness reached 90%. This research will have implications for increasing activities and learning outcomes in class IVB SD Negeri 1 Penatih. Apart from that, it will also have a positive impact, namely the development of learning innovations, one of which is using snake and ladder media.